Combined MvdXML and semantic technologies for green construction code checking - Jiang, Shaohua; Wu, Zheng; Zhang, Bo; Cha, Hee Sung (Applied Sciences (Switzerland), 2019)
The construction process plays a key role in sustainable development of the environment. With the concept of sustainable construction being put forward in the world, some countries released green construction standards to strengthen the requirements in the construction phase. Green construction code checking needs to integrate semantic information embedded in green construction standards and model information involved in Industry Foundation Classes (IFC) and/or Model View Definition (MVD), which are generated separately and lead to difficulty in information integration for green construction code checking. At present, the existing code-checking methods cannot be directly used for green construction. Related practitioners need an efficient and convenient method for green construction code checking urgently. To ameliorate this situation, this research proposes an innovative approach to organize, store, and re-use green construction knowledge by combining mvdXML and semantic technologies. The code checking of green construction is classified into four types based on the difficulty level to meet the requirements of the clauses in green construction standard. Depending on the characteristics of each inspection type, mvdXML or semantic technology is adopted for the appropriate inspection type. This paper demonstrates the deployment and validation of such automated checking procedures in a case study. Based on these experiences, a detailed discussion about the identified issues is provided as the starting point for future research.
Keywords: Code checking; Green construction; MvdXML; Semantic technology